Sustainability of road transportation in Beijing, China - Ang, Lay Ping (2008)
Rapid increase in motorisation has become a trend along with China’s economic development. China announced the Public Transport Policy in 1995 which involved the development of rapid rail and bus transit. According to the Beijing Public Transport Group, the bus system alone catered for four billion person times serving a passenger volume of 4.6 billion in 2007. The concentration of urban population and transportation of passengers and goods are observed to be increasing. Faced with these challenges, intensified efforts were made by the Chinese government to improve the sustainability of transportation systems through transport investments and corrective measures. This paper uses Beijing, the capital of China, passing through a phase of uncontrolled rapid urbanisation and motorisation as the focus of study. The paper first reviews on relevant research to comprehend the concept of a sustainable transport system. The paper then evaluates the existing transportation system and presents the findings to determine if Beijing is moving towards or away from sustainable transportation.